PENERAPAN PENGANGGARAN PARTISIPATIF DI TINGKAT DESA - Slamet Widodo; Dwi Resti Pratiwi (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
Government's commitment to build Indonesia from periphery should be followed by some measures to improve the quality of development planning and budgeting, particularly at the level of village government. The concept of participatory budgeting which has been applied in some countries and in several regions in Indonesia seeks to encourage the active involvement of the community in discussing and prioritizing the local needs and increase the efficiency and effectiveness of budget allocation through a transparent and accountable process. This concept is not intended to replace the Musrenbang process, but it can be done in parallel by different approaches. However, the effectiveness of its implementation depends on the commitment of all parties related to the discussion of the budget at the level of village government.